2011
DOI: 10.17221/229/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of ergosterol and trichothecenes in the grains of three Triticum species

Abstract: Wiwart M., Perkowski J., Budzyński W., Suchowilska E., Buśko M., Matysiak A. (2011)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…In spelt flours, the maximum tolerated contamination is 750 µg/kg. In our study, there are no significant difference in the DON contamination level in both flour types (Schollenberger et al 2002;González-Osnayaa et al 2011;Wiwart et al 2011). The most contaminated products are whole-grains, like bran.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In spelt flours, the maximum tolerated contamination is 750 µg/kg. In our study, there are no significant difference in the DON contamination level in both flour types (Schollenberger et al 2002;González-Osnayaa et al 2011;Wiwart et al 2011). The most contaminated products are whole-grains, like bran.…”
Section: Discussioncontrasting
confidence: 43%
“…The tolerated DON daily intake is 1 µg per 1 kg of body weight per day according to EU determinations (Hussein and Brasel 2001 Wiwart et al (2009) indicated that the average concentration of DON is up to 486.50 µg/kg in spelt kernels and up to 1,508.55 µg/kg on husks. Other authors consistently found lower contamination levels of DON in spelt (Castoria et al 2005;Wiwart et al 2011). Solarska et al (2009) found 169.37 µg/kg as the average concentration of deoxynivalenol in ancient wheats.…”
Section: Discussionmentioning
confidence: 89%
“…This wheat species has been also known for the high resistance to unsupportive environmental factors. Due to a higher stalk and hard adherent husks, spelt has poor fungal infestation in comparison with common wheat (T. aestivum L.) and nowadays is grown mostly by organic methods [33].…”
Section: Triticum Spelta Lmentioning
confidence: 99%
“…Sacc (Parry et al 1995). In Eastern Europe, F. culmorum is the main causal agent of FHB (Jackowiak et al 2005;Wiwart et al 2011). In some years the predominant fungal pathogen on wheat grain is Fusarium poae (Peck) Wollenw.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing mycotoxin contamination of winter wheat grain below the maximum permissible levels in an important consideration, especially in organic wheat production where the use of fungicides is limited. Previous research has focused on breeding of wheat cultivars of different species with increased resistance to fungal infections (Wiwart et al 2011), whereas very few studies have focused on possibility of using yeasts for biological control of Fusarium diseases (Zhang et al 2007). The aim of this study was to determine the effectiveness of A. pullulans in reducing the severity of winter wheat spikes infection caused by F. culmorum, and to analyze the interactions between A. pullulans and F. culmorum on winter wheat grain.…”
Section: Introductionmentioning
confidence: 99%